AKTIVITAS ANTIBAKTERI FRAKSI ETANOL DAUN KEMANGI (Ocimum americanum) TERHADAP Enterococcus faecalis ATCC 29212 - Setiawan, Ame Suciati; Fatriadi, Fajar; Prisinda, Diani (Faculty of Dentistry, Universitas Islam Sultan Agung, 2020)
Background: Ocimum americanum (O. americanum) is a natural plant with antibacterial effects inhibits the growth of gram-positive and gram-negative anaerobic bacteria in the oral cavity. Enterococcus faecalis (E. faecalis) is a gram-positive anaerobic bacteria in the root canal which is resistance to intracanal medicament. The purpose of this study is to analyze the antibacterial effect of ethanol fractionation of O. americanum towards E. faecalis ATCC 29212. Ocimum americanum is a natural plant that has antibacterial properties against grampositive and gram-negative anaerobic bacteria in the oral cavity. Enterococcus faecalis is an anaerobic gram-negative bacteria was found in root canals and resistant to various root canal medicament. The purpose of this study was to analyze the antibacterial effect of the ethanol fraction of Ocimum americanum against Enterococcus faecalis. Methods: The research method was experimental used disc diffusion technique. The fraction is made from solid extract into a polar solution with ethanol solvent with concentration 20%, 40%, 60% and 80%. The test was performed by measuring the inhibition zones around the disc after 24 hours.Results: Chemical properties of O.americanum are alkaloid, flavonoid, saponin, tanin, steroid, dan terpenoid. Inhibition zone of O. americanum fraction with concentration 20%, 40%, 60% and 80% is 8.8 cm, 9.8 cm, 11.1 cm and 16.7 cm. The measurement of O. americanum inhibition zone showed better results compared than positive control (Minosep).Conclusion: Ethanol fraction of O.americanum has antibacterial effect towards E. faecalis.